Adjuvant antifungal therapy using tissue tolerable plasma on oral mucosa and removable dentures in oral candidiasis patients: a randomised double‐blinded split‐mouth pilot study. Issue 7 (2nd March 2016) - Preissner, Saskia; Kastner, Isabell; Schütte, Eyke; Hartwig, Stefan; Schmidt‐Westhausen, Andrea Maria; Paris, Sebastian; Preissner, Robert; Hertel, Moritz
Summary: Extended use of antimycotics in oral candidiasis therapy gives rise to problems related to fungal drug resistance. The aim of this pilot study was to investigate the efficacy of tissue tolerable plasma (TTP) in denture stomatitis patients. It was hypothesised that (I): erythema and (IIa): complaint remission would be accelerated and (IIb): colony forming unit (CFU) reduction would be improved. The halves of the upper jaws of eight patients were randomly assigned to control (nystatin, chlorhexidine and placebo treatment) and test sides (nystatin, chlorhexidine and TTP administered six times each 7 days). The patients and the investigators, who were different from the therapists, were both blinded. Compared to the control sides, the erythema surface was reduced significantly more extensively on the test sides between 2 and 6 weeks of antifungal therapy ( P ≤ 0.05). Visual analogue scale values and the frequency of moderate or heavy growth of Candida post‐treatment did not differ significantly between both sides ( P > 0.05). The primary hypothesis was confirmed, which may be interpreted as an accelerated remission. As drug therapy is usually limited to the time in which signs of infection are present, TTP might help reducing antifungal use. Even though the secondary hypotheses were not confirmed, persistence of Candida might be only colonisation.